Effectiveness of University Leaders’ Behavior and the Faculty Members’ Motivation towards the Work in the Iraqi Colleges of Nursing - Jassim, Basima; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2015)
Objective(s): The present study aims at identifying the Iraqi Colleges of Nursing Deans’ leadership behaviors effectiveness and faculty members’ motivation towards work in these colleges. Methodology: Descriptive design has been used for the sample survey manner, which is the appropriate approach to the study of social phenomena in the field where provides data on the reality of these phenomena and relations between the causes and consequences and an analysis of it and perhaps the factors affecting it and how it appears. The study relies on a questionnaire to collect data from the participants which is composed of (86) items distributed on three axes: First, the demographic characteristics which are composed of (8) items, second, (40) items to measure motivation towards work and the third (38) items to measure the effectiveness of the leadership behavior of the Deans of the Colleges of Nursing. Content validity of the questionnaire is determined through panel of experts who are asked to present their opinion about the content of the questionnaire. The stability has been achieved through the use of reliability coefficients to determine the internal consistency of the questionnaire. Data of the study are collected through field visits to the Iraqi Nursing Colleges and personal interviews with respondents. The study population includes all Iraqi Colleges of Nursing at the time of the study which are distributed through thirteen Governorates. The sample of the study includes (66) subjects who are (55) faculty member and (11) Dean. The sample is purposive "nonprobability" and selected based on the selection criteria to select professor and assistant professor. The study data are analyzed through the descriptive data analysis approach (Frequencies and percentages) and inferential data analysis approach (Chi-square test and Cronbach Alpha Correlation coefficient). The results: The study findings indicate that variables of age groups and years of work have impact upon the improvement of faculty members’ motivation towards work in the Iraqi Colleges of Nursing. Variables of Deans’ age, gender, education, years of work as dean and training have no influence on the leadership behavior of the Colleges of Nursing Deans. Recommendations: The study recommends that we have to promote democratic style practiced by leaders and present freedom and independence of the faculty member because of the stature in the community. The study suggests that there should be an interest for leadership behavior with faculty members, so they can be aware of the desired approaches toward achieving the objectives of the university. The preparation of a proposed program to increase the activation of the performance of faculty in Iraqi Colleges of Nursing and carrying out other studies concerned with this subject and the work of preparing a proposal for the creation of democratic leader in the Iraqi Colleges of Nursing.